2015
DOI: 10.1371/journal.pone.0139986
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Multidrug-Resistant Tuberculosis among Patients with Pulmonary Tuberculosis at the Central Chest Institute of Thailand

Abstract: There are limited data available on the risk factors for multidrug-resistant tuberculosis (MDR-TB). Therefore, we here conducted a retrospective matched case−control study among adults with pulmonary TB who received treatment at the Central Chest Institute of Thailand (CCIT) between January 2007 and December 2013, in order to determine the risk factors associated with MDR-TB among patients with pulmonary TB. We identified 145 patients with pulmonary MDR-TB (cases) and 145 patients with drug-sensitive pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
46
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 39 publications
20
46
1
10
Order By: Relevance
“…We are actively working to (1) increase the sample size of dsptb, (2) analyze and incorporate the mdrptb cases in Shenzhen Center for Chronic Disease Control into our mdrptb case pool, (3) incorporate other imaging features such as cavitary lesion and TB lesion lobular distribution etc into the prediction model. It has been suggested that multiple cavities, particularly those with thick wall, are associated with mdrptb or xdrptb (8, 15).…”
Section: Discussionmentioning
confidence: 99%
“…We are actively working to (1) increase the sample size of dsptb, (2) analyze and incorporate the mdrptb cases in Shenzhen Center for Chronic Disease Control into our mdrptb case pool, (3) incorporate other imaging features such as cavitary lesion and TB lesion lobular distribution etc into the prediction model. It has been suggested that multiple cavities, particularly those with thick wall, are associated with mdrptb or xdrptb (8, 15).…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral cavities were more predominant in both upper zones. Chuchottaworn observed that characteristics of cavities including number of cavities ≥3, the presence of cavities ≥ 2 lung zones were associated with lung multi-drug resistant-tuberculosis (MDR TB) 10 . Manikkam S et al found cavitary lesion in 31.1% 11 .…”
Section: Sexmentioning
confidence: 99%
“…El tiempo de enfermedad es un factor de estudió y se encontró asociado, es así que pacientes con un tiempo de enfermedad mayor a 7 semanas tuvieron 7,27 veces más posibilidades de tener tuberculosis MDR, siendo esta diferencia estadísticamente significativa (Chi cuadrado: p<0,001), resultado concordante con estudios realizados anteriormente, como el realizado por Charoen Chuchottaworn (2015), sobre ''Factores de Riesgo para la Tuberculosis Multidrogoresistente en pacientes con tuberculosis pulmonar en el Central Chest Institute of Thailand'' en donde una duración de la enfermedad mayor a 60 días presento 3,08 más posibilidades de presentar TBC MRD con un IC del 95%: (1,52-6,22)4.…”
Section: Artículo Originalunclassified